Capturing the Mood of Democracy - Coleman, Stephen. author. aut Link
X, 129 p. 30 illus. in color.
Keywords: This book is about what it means to speak of a political mood. Can the electorate be in a mood? How do they express it? How can moods be captured in a meaningful way? This book attempts to answer those questions by looking at one city during the December 2019 British general election. This is not a book about campaign strategies, target voters, turnouts and poll swings. It is about how people feel. The research approach is ethnographic. The telling of the story is lyrical. It may not be hard political science but it contributes significantly to an understanding of the health of contemporary democracy. Focusing upon the ways that voters and non-voters perform their enthusiasm or indifference, the stories that they tell, and photographic images of Bradford in what is supposed to be a vital democratic moment, this book invites readers to engage with the affective texture of an election. .